THE CORRELATION BETWEEN SELF-REGULATED LEARNING TOWARD MATH WITH MATHEMATICAL-LOGICAL THINKING SKIL - AZALINA NURUL FAJARIAH; SRI RAHAYU SETIYORINI ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
The present research aims to analyze the correlation between mathematics Self regulated learning and mathematical-logical thinking skills. The design of the research is survey correlation analysis as it is suitable to validate the relation of the two quantitative variables. To retrieve the data, 60 seventh grade students of two classrooms were sampled through cluster random sampling in SMP PGRI Pameungpeuk. The instruments employed to gather the intended data were logical-mathematical intelligence test consisting of 4 questions and  self regulated learning scale consisting of 25 questions. Further, the data were analyzed in a quantitative manner modeled to logical-mathematical thinking skills data and self regulated learning scale using SPSS 20. The analysis revealed that students’ mathematical Self regulated learning significantly affects students’ logical-mathematical thinking skills.